Economics of Survival Post Trade Secret Misappropriation: Business Insights from Single Firm Event Study on Lexar Media - GUPTA, Rajorshi Sen (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The epic case of Lexar’s trade secret misappropriation by Toshiba (2005) is analyzed. Event study methodology is applied to assess the effect of intellectual property (IP) misappropriation by Toshiba on the value of Lexar. Both parametric tests and non parametric tests are applied to examine the statistical significance of the litigation event on Lexar. It is found that one extant parametric test cannot reject the null hypothesis: Start of litigation event had no effect on Lexar returns. In contrast, non parametric test suggests significant negative impact on Lexar stock price. Both parametric and non parametric tests reject the hypothesis: End of litigation had no effect on Lexar returns. While Lexar stock price fell during the trial commencement, later as Lexar won the litigation, investors updated their belief regarding the validation of its IP. While Lexar continued with supply chain outsourcing strategy, it combated the IP theft problem by producing differentiated products, continuously investing in innovative designs and establishing strategic marketing partnership with Kodak. Companies willing to outsource might invest in product differentiation strategies when it is difficult to protect their IP from theft by outsourcing partners in the presence of weak legal enforcement of contracts.